Implementation of Affective Assessment in History Learning 2013 Curriculum for Class XI IPS at SMA Negeri 3 Temanggung - Wulandari, Aniza Oktarina; Utomo, Cahyo Budi; Suryadi, Andy (Universitas Negeri Semarang, 2022)
The research problems in this study are exploring the history teacher in SMA Negeri 3 Temanggung understanding of affective assessment, examining the implementation of affective assessment by History teacher in SMA Negeri 3 Temanggung, studying problems in the implementation of affective assessment in SMA Negeri 3 Temanggung for History subject. The research employed a descriptive qualitative research method. The interviewees are a History teacher for XI social science class, the vice principal for curriculum, and some XI social sciences graders from SMA Negeri 3 Temanggung—the data collection technique employed observation, interview, and documental study. The validity test is done through source and technique triangulation. Based on the study, it is understood that history teachers' understanding of authentic assessment could be higher. This is proven by the dissents in understanding the definition of authentic assessment, the characteristics, assessment forms, assessment techniques and instruments, and the objective of the authentic assessment. The authentic assessment implementation has yet to be adjusted with the lesson plan, for some practical assessment forms, such as peer assessment, have yet to be implemented. The obstacle in assessing history teachers in SMA Negeri 3 Temanggung is that the 2013 curriculum affective assessment needs to be simplified.